2006
DOI: 10.1158/1541-7786.mcr-06-0042
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Vascular Endothelial Growth Factor Expression by EMMPRIN via the PI3K-Akt Signaling Pathway

Abstract: Extracellular matrix metalloproteinase (MMP) inducer (EMMPRIN) is a cell surface glycoprotein overexpressed in many solid tumors. In addition to its ability to stimulate stromal MMP expression, tumor-associated EMMPRIN also induces vascular endothelial growth factor (VEGF) expression. To explore the underlying signaling pathways used by EMMPRIN, we studied the involvement of phosphoinositide 3-kinase (PI3K)-Akt, mitogen-activated protein kinase (MAPK), JUN, and p38 kinases in EMMPRIN-mediated VEGF regulation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
101
1
3

Year Published

2007
2007
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 114 publications
(111 citation statements)
references
References 23 publications
5
101
1
3
Order By: Relevance
“…Our previous reports have shown that CD147 depletion downregulates MMP-11, VEGF-A expression and the lymphatic metastasis potential of murine hepatocarcinoma Hca-F cells with highly metastatic potential in the lymph nodes (18). Recently, several studies have also demonstrated that there is relationship between CD147 expression and VEGF family, and CD147-mediated VEGF production likely occurs at different levels (2,3). VEGF-A is previously known to act as a specific blood angiogenic factor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous reports have shown that CD147 depletion downregulates MMP-11, VEGF-A expression and the lymphatic metastasis potential of murine hepatocarcinoma Hca-F cells with highly metastatic potential in the lymph nodes (18). Recently, several studies have also demonstrated that there is relationship between CD147 expression and VEGF family, and CD147-mediated VEGF production likely occurs at different levels (2,3). VEGF-A is previously known to act as a specific blood angiogenic factor.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several studies have convincingly demonstrated that CD147 not only plays an important role in tumor progression by inducing MMP production but also stimulates tumor angiogenesis by regulating vascular endothelial growth factor (VEGF) expression (2). Overexpression of CD147 in MDA-MB-231 breast cancer cells regulates VEGF production via the PI3K-Akt signaling pathway (3). Downregulation of CD147 expression by the antisense RNA decreases the secretions of MMP-2, MMP-9, VEGF, and the invasive ability of human glioblastoma cells (4).…”
Section: Introductionmentioning
confidence: 99%
“…Dadurch wird das Wachstum des Tumors in das Blut-oder Lymphsystem ermögli-cht, um von dort in entfernt liegende Organe zu metastasieren. Neben den MMP reguliert EMMPRIN jedoch auch die Expression von VEGF und Hyaluronsäure, wodurch die Tumorangiogenese positiv stimuliert wird und ein höheres Wachstums-und Resistenzverhalten von Tumorzellen ausgelöst wird [21,22].…”
Section: Funktionelle Eigenschaften Und Assoziierte Proteineunclassified
“…So konnte eine indirekte Aktivierung des MAP-Kinase-Weges, der Zellwachstum und Zellüberleben reguliert, durch die Interaktion mit Cyclophilin A (CyPA) demonstriert werden [26]. In Mammakarzinomzellen konnte nachgewiesen werden, dass eine erhöhte Expression von EMMPRIN sowohl den MAP-Kinase-Weg als auch den Phosphoinositol-3-Kinase-(PI3 K-)Weg stimuliert [21]. Dabei wurde in Fibroblasten gezeigt, dass dieser Effekt mit lös-lichem, also extrazellulärem EMMPRIN ausgelöst werden kann und nicht nur den PI3 K-Signalweg aktiviert, sondern auch zu einer Expression des Wachstumsfaktors VEGF führt, der die Angiogenese auslöst [21].…”
Section: Funktionelle Eigenschaften Und Assoziierte Proteineunclassified
See 1 more Smart Citation